Efficacy and safety of inhaled ambroxol solution in improving sputum of lower respiratory tract infection in children: a multicenter, randomized, double-blind, placebo-controlled trial - Xu, Baoping; Han, Peng; Shang, Yunxiao; Cheng, Huanji; Han, Zhiying; Zhao, Lin; He, Shaoru; Lu, Min; Liu, Enmei; Shen, Kunling (BMC pulmonary medicine, 2025)
To evaluate the efficacy and safety of inhaled ambroxol solution in improving sputum of lower respiratory tract infections (LRTIs) in children. This study was a randomized, double-blind, parallel-group, placebo-controlled, multicenter trial. The patients were administered inhaled ambroxol or a placebo twice a day for 7 days. And researchers collected efficacy and (or) safety indicators every day during the course. A total of 236 children were randomly assigned to receive ambroxol or placebo (1:1). At all visit points after the medication, the mean difference of cough score with the baseline between the two groups was statistically significant (P < 0.05). Compared with the baseline, the phlegm-sound scores in the throat of the experimental group decreased more on the 1st, 2nd, and 3rd days after administration (P < 0.05). But there was no difference in pulmonary rale scores. The occurrence of adverse events in the experimental group was lower (21.37% vs. 35.59%, P = 0.021), and the incidence of adverse reactions was similar between the two groups (2.56% vs. 5.08%, P = 0.499). Inhaled ambroxol solution could improve the sticky sputum symptoms in children with LRTIs and is safe in clinical application. Further research is needed to confirm these findings. The study was retrospectively registered on June 14, 2023, at https://www.chictr.org.cn/ under the number ChiCTR2300072466.